2017
DOI: 10.29054/apmc/17.400
|View full text |Cite
|
Sign up to set email alerts
|

Management of Forgotten Ureteral Double J Stents: Causes and Management

Abstract: Introduction: Double J stent (DJS) is a basic and valuable tool in urological practice. A forgotten DJS is not uncommon and is associated with significant morbidity and mortality. The presenting complaints may range from UTI to renal failure. Therefore, this study has been carried out to assess the clinical spectrum of this entity in our setting. Objective: To describe the clinical presentation, complications and management of forgotten DJS. Methods: This retrospective descriptive study was done at the Departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Only three of our present patients (2.3%) required open surgery, as the stent could not be removed after four sessions of ESWL due to the longevity of stent indwelling (~5 years) and its location (the whole length of the stent). Anwar et al [15] showed that 87.5% of their study cases were managed endoscopically with a 43.8% success rate with a single cystoscopic procedure, whilst combined ESWL with endoscopic procedures was required in rest of the cases (43.6%). The open procedure was required in two cases following failed attempted URL.…”
Section: Discussionmentioning
confidence: 97%
“…Only three of our present patients (2.3%) required open surgery, as the stent could not be removed after four sessions of ESWL due to the longevity of stent indwelling (~5 years) and its location (the whole length of the stent). Anwar et al [15] showed that 87.5% of their study cases were managed endoscopically with a 43.8% success rate with a single cystoscopic procedure, whilst combined ESWL with endoscopic procedures was required in rest of the cases (43.6%). The open procedure was required in two cases following failed attempted URL.…”
Section: Discussionmentioning
confidence: 97%
“…Patients should be appropriately informed and made aware of the significance of stent presence. Economic issues are also a key source of concern in emerging countries such as ours (19) . Nevertheless, Jhanwar et al (20) observed that the most common reason for residual DJS was poor patient counseling on the side of the surgeon (38.16%).…”
Section: Discussionmentioning
confidence: 99%